2018
DOI: 10.1002/aenm.201702165
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Polymer Homo‐Tandem Solar Cells with Carbon Quantum‐Dot‐Doped Tunnel Junction Intermediate Layer

Abstract: The tunnel junction (TJ) intermediate connection layer (ICL), which is the most critical component for high‐efficient tandem solar cell, generally consists of hole conducting layer and polyethyleneimine (PEI) polyelectrolyte. However, because of the nonconducting feature of pristine PEI, photocurrent is open‐restricted in ICL even with a little thick PEI layer. Here, high‐efficiency homo‐tandem solar cells are demonstrated with enhanced efficiency by introducing carbon quantum dot (CQD)‐doped PEI on TJ–ICL. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Raïssi et al showed an ICL consisting of PEDOT:PSS, on top of which they deposited an ETL made from a mixture of single‐walled carbon nanotubes (SWNT) and a phthalocyanine derivative (TSCuPc), and the sole phthalocyanine . Another form of carbon for the ICL is carbon quantum dots (CQDs), mixed with PEI as described by Kang et al CQDs were synthesized by a microwave reaction starting from citric acid and β‐alanine, resulting in particles with a size of ≈3 nm. A thin layer of the CQDs/PEIE composite on top of PEDOT:PSS was reported to provide an efficient tunneling junction for the recombination of charges in the ICL, affording a best efficiency of 12.1%.…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raïssi et al showed an ICL consisting of PEDOT:PSS, on top of which they deposited an ETL made from a mixture of single‐walled carbon nanotubes (SWNT) and a phthalocyanine derivative (TSCuPc), and the sole phthalocyanine . Another form of carbon for the ICL is carbon quantum dots (CQDs), mixed with PEI as described by Kang et al CQDs were synthesized by a microwave reaction starting from citric acid and β‐alanine, resulting in particles with a size of ≈3 nm. A thin layer of the CQDs/PEIE composite on top of PEDOT:PSS was reported to provide an efficient tunneling junction for the recombination of charges in the ICL, affording a best efficiency of 12.1%.…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…When blended with PC 70 BM, an efficiency of 11.3% was reported for a homo‐tandem device with this active layer despite the lack of complementarity in the absorption due to the use of the same absorber for both the front and back subcells . More groups reported similar efficiencies for tandem cells featuring this blend in one of the two subcells . Zheng et al combined the polythiophene PDCBT and the benzodithiophene‐based PBDT‐TS1, blended with PC 70 BM and PC 60 BM, respectively in a tandem device .…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…[32] www.advmat.de www.advancedsciencenews.com Adv. The LED (λ = 635 nm) provided both the DC and AC components of the illumination, where the modulation depth of the AC component superimposed on the DC light was 10%.…”
Section: Methodsmentioning
confidence: 99%
“…[25] To get rid of this obstacle, an interlayer between the electrodes and organic layers is applied to facilitate the transfer of charges in organic devices. [31,32] Among different interlayer materials used so far, zwitterionic materials have been proved Zwitterions, a class of materials that contain covalently bonded cations and anions, have been extensively studied in the past decades owing to their special features, such as excellent solubility in polar solvents, for solution processing and dipole formation for the transfer of carriers and ions. While in the case of OSCs and PVSCs, apart from the enhancement in charge injection, they also play an important role to increase the built-in electric field across the active layer, ensuring efficient extraction of photogenerated charge carriers.…”
Section: Doi: 101002/aenm201803354mentioning
confidence: 99%
“…[25] To get rid of this obstacle, an interlayer between the electrodes and organic layers is applied to facilitate the transfer of charges in organic devices. [31,32] Among different interlayer materials used so far, zwitterionic materials have been proved While in the case of OSCs and PVSCs, apart from the enhancement in charge injection, they also play an important role to increase the built-in electric field across the active layer, ensuring efficient extraction of photogenerated charge carriers.…”
mentioning
confidence: 99%